Heat transfer and pressure loss characteristics of an offset fin with oblique waves. (January 2023) - Gong, Jiaming; Onishi, Junya; Komatsu, Yosuke; Mao, Ning; Kametani, Yukinori; Hasegawa, Yosuke; Shikazono, Naoki
Hightlight: The configurations of OFOW induce strong secondary flow at the leading edge, and the secondary flow remains considerably strong throughout the plate. The coupling of intensified secondary flow and leading-edge effects significantly enhances heat transfer, though suffers from increased pressure loss penalty. Both V wave pointing directions in the second plate can only induce fragmentized vortices, which results in the weakened interaction of the fluids between the sidewalls and channel center. Wave amplitude A is the most dominant parameter. When A  = 0.3 at Re ≈ 400, j of OFOWs is 4.2 times enhanced than the plain channel and 1.8 times than the OSF, while f is 5.5 times larger than the plain channel and 2.3 times than the OSF. Area goodness factor j/f is only 20% smaller than the plain channel and 24% smaller than the OSF, while JF is enhanced by 155% than the plain channel and 34% than the OSF. Wave pointing direction and phase angle in the successive offset plates have minor effects. At the same amplitude A, the four configurations of OFOW show comparable heat transfer and pressure loss characteristics. Abstract: An offset fin with oblique waves (OFOW) which is a combination of offset fin (OSF) and V-shaped oblique wavy fin (OWF) has been proposed to further enhance heat transfer in single phase laminar flows. The heat transfer and pressure loss characteristics of different configurations of the OFOW are investigated numerically. The 3D unsteady periodic model with the H1 thermal boundary condition is adopted to explore the effects of V wave pointing direction, phase angle and wave amplitude. The local distributions of velocity, secondary flow, wall shear stress and heat flux as well as friction factor f and Colburn factor j are presented and compared with those of the plain channel, OSF and OWF with the same aspect ratio and hydraulic diameter. It is found that the OFOW can further enhance heat transfer than the OSF and OWFs, i.e., at Re ≈ 400 with wave amplitude of A  = 0.3, the Colburn factor j is around 4.2 times of that of the plain channel. It is shown that opposite V wave pointing directions in the successive offset plates cannot induce long-range counter-rotating vortices, and V wave amplitude A is the most dominant parameter, where wave pointing direction and phase angle in the successive offset plates have minor effects.